2013
DOI: 10.1038/npp.2013.218
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity and Risk Taking in Bipolar Disorder and Schizophrenia

Abstract: Impulsive risk taking contributes to deleterious outcomes among clinical populations. Indeed, pathological impulsivity and risk taking are common in patients with serious mental illness, and have severe clinical repercussions including novelty seeking, response disinhibition, aggression, and substance abuse. Thus, the current study seeks to examine self-reported impulsivity (Barratt Impulsivity Scale) and performance-based behavioral risk taking (Balloon Analogue Risk Task) in bipolar disorder and schizophreni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
112
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(142 citation statements)
references
References 44 publications
12
112
4
1
Order By: Relevance
“…Our sample's scores are similar to those found in people with personality disorders and in other psychiatric patients (Fossati et al, 2015), but are higher than the average score found in a sample of patients with schizophrenia (Troisi, 2011). However, the BIS-11 total score collected in our study in both groups is much higher than that of healthy controls, who recently reported scores ranging between 37.9 and 42.9 (Reddy et al, 2014;Zhornitsky et al, 2012). Concerning the history of aggressive behaviour assessed by BGLHA, mean scores were comparable to those of male prisoners in the control group (Bevilacqua et al, 2012; Carli et al, 2010; a Statistically significant differences (p < 0.05) between violent and control patients at the same timepoint (baseline).…”
Section: Impulsiveness and Aggressivenesssupporting
confidence: 76%
“…Our sample's scores are similar to those found in people with personality disorders and in other psychiatric patients (Fossati et al, 2015), but are higher than the average score found in a sample of patients with schizophrenia (Troisi, 2011). However, the BIS-11 total score collected in our study in both groups is much higher than that of healthy controls, who recently reported scores ranging between 37.9 and 42.9 (Reddy et al, 2014;Zhornitsky et al, 2012). Concerning the history of aggressive behaviour assessed by BGLHA, mean scores were comparable to those of male prisoners in the control group (Bevilacqua et al, 2012; Carli et al, 2010; a Statistically significant differences (p < 0.05) between violent and control patients at the same timepoint (baseline).…”
Section: Impulsiveness and Aggressivenesssupporting
confidence: 76%
“…Risk propensity and impulsivity are associated with ADHD (Bakhshani 2013;Drechsler et al 2008;Shoham et al 2016), bipolar spectrum conditions (Alloy et al 2012;Reddy et al 2014;Strakowski et al 2010;Swann et al 2001), substance use disorders (Birkley and Smith 2011;Feldstein and Miller 2006;Kreek et al 2005;Lejuez et al 2010), and the cooccurrence of these conditions (Holmes et al 2009;Lee et al 2011;Moeller et al 2001;Upton et al 2011;Zuckerman and Kuhlman 2000). Akiskal et al (2005) studied 263 professionals affiliated with an outpatient psychiatric practice.…”
Section: Risk Propensitymentioning
confidence: 99%
“…Increased engagement in risk-taking behaviors is found in psychiatric disorders such as BD, schizophrenia and substance abuse [15,22], and has been studied in animal models for psychiatric disorders [19,24,30,27]. Repeated amphetamine treatment was found to increase risk-taking behavior [14,34].…”
Section: Introductionmentioning
confidence: 99%